FtsK and SpoIIIE, coordinators of chromosome segregation and envelope remodeling in bacteria. Issue 5 (May 2022) - Chan, Helena; Mohamed, Ahmed M.T.; Grainge, Ian; Rodrigues, Christopher D.A.
Abstract : The translocation of DNA during bacterial cytokinesis is mediated by the SpoIIIE/FtsK family of proteins. These proteins ensure efficient chromosome segregation into sister cells by ATP-driven translocation of DNA and they control chromosome dimer resolution. How FtsK/SpoIIIE mediate chromosome translocation during cytokinesis in Gram-positive and Gram-negative organisms has been the subject of debate. Studies on FtsK in Escherichia coli, and recent work on SpoIIIE in Bacillus subtilis, have identified interactions between each translocase and the division machinery, supporting the idea that SpoIIIE and FtsK coordinate the final steps of cytokinesis with completion of chromosome segregation. Here we summarize and discuss the view that SpoIIIE and FtsK play similar roles in coordinating cytokinesis with chromosome segregation, during growth and differentiation. Highlights: A recent study shows that SpoIIIE interacts with proteins that are connected to the cell envelope during spore development. FtsK appears to interact with proteins within all layers of the Gram-negative cell envelope. SpoIIIE and FtsK are both multifunctional and they coordinate cell-envelope remodeling with chromosome segregation. Both SpoIIIE and FtsK likely regulate peptidoglycan remodeling at the septum. Advances in cryo-electron microscopy may reveal how FtsK and SpoIIIE complexes are organized during cytokinesis.